(untitled) (Vietnam Journal of Community Medicine, 2026)
Heterotopic pregnancy is the simultaneous occurrence of an intrauterine pregnancy and an ectopic pregnancy. It is a rare condition in natural conception but has shown a marked increase with the widespread use of assisted reproductive technologies. Interstitial ectopic pregnancy is a particularly dangerous form due to the risk of delayed rupture and massive hemorrhage. We report a rare case of heterotopic pregnancy consisting of a viable intrauterine pregnancy and a right interstitial tubal pregnancy following in vitro fertilization in a patient with a history of right salpingectomy. The patient was diagnosed early by ultrasonography and promptly managed with laparoscopic surgery, allowing preservation of the intrauterine pregnancy. The pregnancy progressed favorably and was completed by term cesarean delivery with a healthy newborn. This case highlights the importance of early diagnosis of heterotopic pregnancy (a viable intrauterine pregnancy and an interstitial tubal pregnancy) in patients who conceive after assisted reproductive techniques, even in those with a history of salpingectomy, to enable timely surgical management and achieve favorable outcomes for both the mother and the intrauterine pregnancy.